A PERCEPÇÃO DE DELÍRIO E FORMAS DE INTERVENÇÃO DE PROFISSIONAIS DE SAÚDE - BASTOS, ISAAC SOARES (2017)
Being influenced by movements that arose mainly in France, England and Italy, care services for people suffering from some form of severe psychological distress have undergone through significant changes that favored the construction of new health paradigms, as well as new care devices. Such events brought about fairly fresh political, administrative and technical demands — as well as theoretical ones — that laid the groundwork for the construction of a novel field of knowledge that was diverse and heterogeneous (that one of the mental health), in which both worker and user reassessed their conceptions and practices regarding psychopathologies and their ways to treat them. Given this context, the present study had as its objective to verify how the CAPS worker perceives and intervenes before the user who presents or has presented a delirium state. Data were collected by using a socio-demographic questionnaire, a semi-structured interview technique and the participant observation. On the basis of proposals elaborated by Bardin, for the analysis and treatment of the data it was employed the Content Analysis technique. The data have revealed that the perception of the professional is created from conceptual axes, which we are going to divide into dualism of reality, nosographic, neurological, contextual and psychoanalytic. And it is from these axes that their intervention is configured. However, such axes are not demarcated or delimited in their theoretical or epistemological framework. They intersect and cross each other, producing a blended, eclectic intervention that sometimes is also done or based only on the experience and commitment of the professional.